Developing Democratic Participation Through Civil Liberties Education in Social Studies Classrooms - Earnhart, Geoffrey L. (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Social studies educators must prepare students for the challenges of a changing world by providing them content knowledge and developing attitudes conducive to participatory citizenship. Most future government policies will have civil liberties implications, thus studying these issues provides a firm foundation for future decision making. Teachers should approach this content using student-centered methods in an open classroom climate in order to build students’ political efficacy that they will need for the future. These techniques equip students to be informed decision makers and encourages them to participatory citizens in later life.